Избранные сочинения - Крылов Иван Андреевич (Библиотека мировой литературы для детей, 1995)
Экземпляры: ф. 15 (20221028) / Инвентарный номер: 31930 / Цена: 69.00 / Авт.знак: К 85 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1